Prediction of Rupture by Complete Blood Count in Tubal Ectopic Pregnancies Treated with a Single-Dose Methotrexate Protocol - Yıldız Akdaş Reis; Arife Akay; Elif Gülşah Diktaş; Merve Özkan; Neslihan Öztürk; Doğukan Özkan; Betül Tokgöz Çakır; Salim Erkaya (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective The availability of reliable and inexpensive markers that can be used to determine the risk of rupture during methotrexate (MTX) treatment in ectopic pregnancies (EPs) is considerable. The aim of the present study is to investigate the role of systemic inflammatory markers such as leukocytes (or white blood cells, WBCs), the neutrophil-to-lymphocyte ratio (NLR), and platelet distribution width (PDW), which are among the parameters of the complete blood count (CBC), in the prediction of rupture of EPs under MTX treatment. Materials and Methods A total of 161 patients with tubal EP who underwent a single-dose methotrexate (MTX) protocol were retrospectively analyzed, and the control group (n = 83) included patients cured by MTX, while the ruptured group (n = 78) included patients who were operated on for tubal rupture during the MTX treatment. The features of EP, beta-human chorionic gonadotropin (β-hCG) levels, sonographic findings, and CBC-derived markers such as WBC, NLR, and PDW, were investigated by comparing both groups. Results The NLR was found to be higher in the ruptured group, of 2.92 ± 0.86%, and significantly lower in the control group, of 2.09 ± 0.6%. Similarly, the PDW was higher (51 ± 9%) in the ruptured group, and it was significantly lower a (47 ± 13%) in the control group (p < 0.05). Other CBC parameters were similar in both groups (p > 0.05). Conclusion Systemic inflammation markers derived from CBC can be easily applied to predict the risk of tubal rupture in Eps, since the CBC is an inexpensive and easy-to-apply test, which is first requested from each patient during hospitalization.